Long-Term Esthetically Depigmented Gingiva in a Short Operative Duration, Using Two Modes of 940 nm Diode Lasers-A Randomized Clinical Trial - Baydaa F. Hamzah; Abrar N. Alattar; Tiba A. Salman (Hindawi Limited, 2022)
Aim. This study aims to compare the effectiveness of the two modes of 940 nm diode lasers on gingival depigmentation. Methods. Twenty patients (11 females and 9 males) participated in this study; they were free of any systemic or local condition and randomly assembled into two groups: continuous wave (CW) and pulsed groups, in contact modes. The diode laser was of 940 nm wavelength and 1-2 W irradiation power for the two modes in all cases. A single session of irradiation was applied to the facial gingivae of the upper and lower anterior segments. Photographs were taken preoperatively and postoperatively for all patients, and a questionnaire and follow-up were carried out for the next four weeks and after three years. Results. The intraoperative duration of both modes was considerably short, with a short chair time subsequently. A statistically significant decrease in the intensity of pain, discomfort, and bleeding p≤0.05 was noticed during the first week of follow-up within each group. Nonetheless, the two groups showed a close pattern of decline with no statistically significant differences between them. It was also clear that pain and discomfort were strongly correlated with each other within each group, and the correlation was statistically significant. On the other hand, carbonization was minimal in a few cases treated with CW mode but still not statistically significant. Finally, although the gingival pigmentation index (GPI) differences were not statistically significant between the two groups, they were significant within each group. Conclusions. The diode laser (940 nm) offered an effective and safe modality, providing an optimal aesthetic result that can meet patient satisfaction with minimal pain, bleeding, discomfort, intraoperative time, and the possibility of recurrence in the treatment of gingival hyperpigmentation.